Metode Bervariasi Oleh Guru PAK Terhadap Motivasi Belajar Siswa - Hotmauly Munthe (Institut Agama kristen Negeri Tarutung, 2021)
Abstract: Students in class often lack motivation to study Christian religious education, it can also be due to boring learning methods. This is indicated by students not paying serious attention, not being diligent in doing assignments, being lazy, noisy during the teaching and learning process, and even not wanting to ask the teacher for material they have not understood. The lack of student learning motivation is influenced by several factors that influence student learning motivation, namely: student goals and aspirations, student abilities, student environmental conditions, dynamic elements in learning and learning, teacher efforts in teaching students